Adenocarcinoma da ampola de Vater associado com neurofibromatose de von Recklinghausen. - Gomes, H; Lebre, R; Fonseca, J; Borralho, P; Duarte, R (Acta Médica Portuguesa, 1997)
Von Recklinghausen's Neurofibromatosis is an autosomal dominant disease of variable manifestations. Association with gastrointestinal and hepatobiliary tumours is well documented, most of them being benign neurofibromas. Other tumours, such as leiomyomas, sarcomas, ganglioneuromas and carcinoids are less frequent. Much rarer is the development of epithelial malignancies and an ontogenic relation is not clear. The authors reports a case of adenocarcinoma of Vater's Ampulla and duodenal neurofibromas, in a patient with Von Recklinghausen's disease, presenting obstructive jaundice.